Gender effect on E-commerce sales of experience gifts: Preliminary empirical findings - Joni Salminen; Sarem Seitz; Bernard J. Jansen; Tommi Salenius (My University, 2022)
We analyze purchase data from 493 customers of an e-commerce store selling experience gifts to find how gender correlates with average purchase value, category of purchased products, and the use of discount codes. We find no significant differences for average purchase value or category of purchased products, but according to the data, women are more likely to use discount codes than are males. Ideas for further research concerning the gender effect on online shopping behavior are discussed.
17th International Conference on Electronic Business: Smart Cities, ICEB 2017